2004
DOI: 10.1023/b:johe.0000016715.91811.4b
|View full text |Cite
|
Sign up to set email alerts
|

Improving Physician Coverage of Pneumococcal Vaccine: A Randomized Trial of a Telephone Intervention

Abstract: Improved pneumococcal vaccine (PPV) immunization for seniors is a national goal of the Medicare program. This study examined whether adding a simple telephone follow-up to an existing mailed physician performance feedback under the Medicare program would increase the impact on billed pneumococcal immunizations. Medicare fee-for-service claims data were used to select New York primary care physicians with high volume (n = 732) or African-American serving (n = 329) practices. All practices received mailed feedba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 7 publications
0
13
0
Order By: Relevance
“…Some strategies that have proved useful in improving vaccination coverages and should therefore be assessed, include: monitoring the vaccination status of persons with chronic diseases; increasing and improving information on the risks of pneumococcal disease and the benefits of the vaccine for patient and health professional alike; enhancing the use of regular (postal or telephone) reminders in the case of high-risk subjects; and continuing to insist on raising the general practitioners' awareness as to the vital importance of their advice vis-à-vis risk groups. 10,35,67 In addition, it has been shown that making use of the annual influenza vaccination campaigns to detect and vaccinate as yet unvaccinated high-risk subjects against pneumococcus is an effective strategy for increasing pneumococcal vaccination coverages. 39,41,42 Accordingly, the conclusions to be drawn from this study are: that pneumococcal vaccination coverages among Spanish COPD patients are low; and that strategies to improve these must be implemented as a matter of urgency.…”
Section: Discussionmentioning
confidence: 99%
“…Some strategies that have proved useful in improving vaccination coverages and should therefore be assessed, include: monitoring the vaccination status of persons with chronic diseases; increasing and improving information on the risks of pneumococcal disease and the benefits of the vaccine for patient and health professional alike; enhancing the use of regular (postal or telephone) reminders in the case of high-risk subjects; and continuing to insist on raising the general practitioners' awareness as to the vital importance of their advice vis-à-vis risk groups. 10,35,67 In addition, it has been shown that making use of the annual influenza vaccination campaigns to detect and vaccinate as yet unvaccinated high-risk subjects against pneumococcus is an effective strategy for increasing pneumococcal vaccination coverages. 39,41,42 Accordingly, the conclusions to be drawn from this study are: that pneumococcal vaccination coverages among Spanish COPD patients are low; and that strategies to improve these must be implemented as a matter of urgency.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have observed a similar weak effect of physician education and chart reminders to improve vaccination rates. [14][15][16][17] Even if physicians gain requisite knowledge of vaccination indications through educational interventions, that knowledge often does not translate into improved clinical practices. 18 A more active physician educational interaction through the Delphi survey improved understanding and acceptance of pneumococcal vaccination.…”
Section: Discussionmentioning
confidence: 99%
“…These are summarised in Appendix 16, Figure 21. Most of these involved social comparison in both arms, with feedback on behaviour 20,[70][71][72][73][74][75][76][77] or without feedback 18 (n = 10), and typically they were studies that tested some other combination of BCTs in the intervention arm, but had A&F offered as part of usual care in both arms. One study tested a combination of BCTs in the intervention arm, but had credible source in both arms as part of usual care.…”
Section: Studies With Social Norms Behaviour Change Techniques In Both Armsmentioning
confidence: 99%
“…Colon-Emeric 2007 120 Curtis 2005 121 Low risk of bias Unclear High risk of bias Curtis 2007 122 Desveaux 2016 77 Vellinga 2016 61 Eccles 2001 123 Elouafkaoui 2016 124 Eltayeb 2005 125 Ferguson 2003 126 Fiks 2017 127 Foster 2007 128 Foy 2004 129 French 2013 64 Fuller 2012 130 Gerber 2013 131 Lakshminarayan 2010 63 Leviton 1999 65 Liddy 2011 144 Lim 2018 145 Lomas 1991 67 MacLean 2009 102 Mayne 2014 146 Goff 2002 133 Guadagnoli 2000 68 Guldberg 2011 93 Hallsworth 2016 60 Hayashino 2016 134 Hayes 2002 69 Heller 2001 135 Hemkens 2017 136 Patel 2018 155 Peiris 2015 101 Persell 2016 62 Pimlott 2003 156 Pope 2010 91 Quinley 2004 72 Raasch 2000 157 Raja 2015 92 Rask 2001 78 Søndergaard 2003 161 Sandbaek 1999 158 Sauaia 2000 80 Schneider 2008 83 Butler 2012 118 Soleymani 2014 159 Søndergaard 2002 160 Soumerai 1998 79 Tjia 2015 164 Trietsch 2017…”
Section: Information About Others' Approvalmentioning
confidence: 99%